Validation of key indicators in cattle farms at high risk of animal welfare problems: a qualitative case‐control study. (23rd March 2013) - Kelly, P. C.; More, S. J.; Blake, M.; Higgins, I.; Clegg, T.; Hanlon, A.
Abstract : The objective of this study was to validate four key farmer performance indicators (KFPI), identified in a previous study, as indicators of on‐farm cattle welfare incidents in Ireland, through comparison of the distribution of these KPFIs in the national herd (n=109, 925) and in case herds (n=18), where welfare incidents were previously studied. The KFPIs identified were late registrations, and exits from the herd by on‐farm burial, by moves to knackeries and by moves to 'herd unknown'. Data were extracted from two Department of Agriculture, Food and the Marine databases for the national herd and the case herds. All four KFPIs differed significantly between the case herds and the national herd, and one further KFPI was identified, namely moves to factories. The data for these KFPIs are routinely stored on national databases, which were established in order to comply with Regulation (EC) 1760/2000. Based on the results obtained in this study, it may be possible in the future to use routine data capture to improve strategy towards on‐farm animal welfare. At this point, however, based on calculated specificities and sensitivities, none of these five KFPIs, at the cut‐offs investigated and using several combinations, are able to distinguish herds with and without on‐farm animal welfare problems at an accuracy suitable for routine national use in Ireland.